RASIO KEUANGAN DAN PERUBAHAN LABA PERUSAHAAN AGROINDUSTRI DI BURSA EFEK INDONESIA - Nindhika Paramawardhani; Tatang Ary Gumanti; Novi Puspitasari (RELASI : JURNAL EKONOMI, 2014)
This research is intended to evaluate the relationship between financial ratios and profit change. The financial ratios examined in this study include Current Ratio (CR), Working Capital to Total Asset (WCTA), Debt to Equity Ratio (DER), Current Liability to Inventory (CLI), Operating Income to Total Liabilities (OITL), and Total Asset Turnover (TATO). Profit change is measured as the different between gross profit in year t and year t-1. Sample used in this research is firm in agroindustry sector listed at Indonesia Stock Exchange. The selection ofagroindustry firm is based on the contribution in Indonesia economy. Population of agroindustry company was 21 in which 12 company were selected as the sample. The data cover a period from 2008-2012. The technique of analyses to test the hypotheses was multiple linier regression. The results of this research indicate that Debt to Equity Ratio (DER) and Operating Income to Total Liabilities (OITL) are positive significantly effect profit change, while Current Ratio (CR), Working Capital to Total Asset (WCTA), Current Liability to Inventory (CLI), and Total Asset Turnover (TATO) aren’t significantly effect profit change.